COMPARISON OF DATA MINING CLASSIFICATION TECHNIQUES FOR HEART DISEASE PREDICTION SYSTEM - Rezty Amalia Aras; Noor Akhmad Setiawan (Pusat Riset dan Inovasi Nasional, 2022)
DM is the process of analyzing data from different perspectives and gathering knowledge that can be used for different applications. Classification as one of the data mining techniques used to predict group membership. For example, the healthcare industry. DM provides a set of techniques for discovering hidden patterns from data. In this paper, we examine the heart disease dataset in order to obtain information or patterns that can be useful for making a decision. The test in this paper is a prediction of heart disease using three classification methods, namely OneR, decision tree and naive bayes. The results of this experiment show predictions from each experiment with different levels of prediction accuracy in each method used with 91.48% accuracy for the decision tree, 85.18% for naive Bayes and 76.3% for OneR.